The value of archival tissue blocks in understanding breast cancer biology. Issue 3 (29th October 2013) - Dowsett, Thomas; Verghese, Eldo; Pollock, Steven; Pollard, Jennifer; Heads, Judith; Hanby, Andrew; Speirs, Valerie
Abstract : Pathological reporting of breast cancer has evolved alongside scientific advances. Such advances have led to recognition of different molecular classes of breast cancer resulting in improved disease management. The aim of this study was to establish whether these advances could be applied to archival breast cancer cases dating from the 1940s to assess historical trends. Important observations included the marked differences in pathological reporting, size of tumour and in ERα expression throughout the decades.